2020
DOI: 10.1021/jacs.0c04705
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Modulation of Dynamic Imine Libraries Driven by the Hexameric Resorcinarene Capsule

Abstract: The composition of dynamic covalent imine libraries (DCL) adapts to the presence of the hexameric resorcinarene capsule. In the presence of the self-assembled capsule, a kinetic and thermodynamic modulation of the imine constituents of the DCLs was observed, which was induced by an unusual predatory action of the capsule on specific imine constituents. More complex 2 × 2 DCLs also adapt to the presence of the hexameric capsule, showing a thermodynamic and kinetic modulation of the constituents induced by the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 61 publications
0
30
0
Order By: Relevance
“…Finally, after 24 h the 69 / 70 ratio reached the value of 15/60 and remained constant (48 h). These results indicated that 69 was the kinetically favoured product, while 70 was the thermodynamic one [47] …”
Section: Supramolecular Catalysis In Confined Spacementioning
confidence: 87%
See 3 more Smart Citations
“…Finally, after 24 h the 69 / 70 ratio reached the value of 15/60 and remained constant (48 h). These results indicated that 69 was the kinetically favoured product, while 70 was the thermodynamic one [47] …”
Section: Supramolecular Catalysis In Confined Spacementioning
confidence: 87%
“…Differently, the formation of the complex 70 @ C R is unfavoured in enthalpic as well as Gibbs free energy terms [47] . QM calculations indicated that the encapsulation of imine 69 inside C R was driven by the formation of a H‐bonding interaction (Figure 6) between the nitrogen atom of 70 and a bridging water molecule.…”
Section: Supramolecular Catalysis In Confined Spacementioning
confidence: 99%
See 2 more Smart Citations
“…17,18 The eld has been reviewed, [19][20][21][22][23] and novel applications have been found very recently. [24][25][26][27] In 2016, our group reported that iminium-catalysis can be performed inside capsule I (Fig. 1b).…”
Section: Introductionmentioning
confidence: 99%